Can Simple Psychological Interventions Increase Preventive Health Investment? - Haushofer, J; John, A; Orkin, K (National Bureau of Economic Research, 2019)
Behavioral constraints may explain part of low demand for preventive health products. We test the effects of two light-touch psychological interventions on water chlorination and related health and economic outcomes using a randomized controlled trial among 3750 women in rural Kenya. One intervention encourages participants to visualize alternative realizations of the future; one builds participants' ability to make concrete plans to achieve goals. Both interventions include information on health benefits of chlorination. After twelve weeks, both interventions increase the share of households who chlorinate drinking water and reduce child diarrhea episodes. Analysis of mechanisms suggests both interventions increase self-efficacy – beliefs about one's ability to achieve desired outcomes – as well as the salience of chlorination. They do not differentially affect beliefs and knowledge about chlorination (compared to a group who receive only information), nor affect lab measures of time preferences or planning ability. Results suggest simple psychological interventions can increase use of preventive health technologies.